Long‐term utility outcomes in patients undergoing endoscopic sinus surgery. (13th May 2013) - Rudmik, Luke; Mace, Jess; Soler, Zachary M.; Smith, Timothy L.
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis To define long‐term health‐state utility outcomes in patients undergoing endoscopic sinus surgery (ESS) for refractory chronic rhinosinusitis (CRS). Study Design Prospective, longitudinal, cohort study. Methods The short‐form (SF)−12 survey was issued to the 168 patients who were enrolled in an initial study evaluating short‐term utility outcomes following ESS. SF‐12 responses were converted into SF‐6D utility scores using the University of Sheffield algorithm. The primary outcome was mean overall long‐term utility level following ESS. Secondary outcomes evaluated annual utility level following ESS and utility outcomes for different subgroups of patients with CRS. Results A total of 83 patients provided long‐term health‐state utility outcomes. The mean overall long‐term utility level was 0.80 at a mean follow‐up of 5.2 years after ESS. Compared to the baseline (0.67) and short‐term follow‐up (0.75) utility levels in this group, there was a significant improvement at the long‐term period (P = .002). A total of 54% (45/83) of patients achieved long‐term postoperative utility scores higher than the United States norm of 0.81. There was a significant improvement in utility scores for all subsequent years after ESS compared to preoperative responses (all P < .028). All subgroups of CRS received significant long‐term utility improvements (all P < .001), and those undergoing revision ESS demonstrated continued improvement past the short‐term postoperative period. Conclusions This study has demonstrated that patients with refractory CRS achieve stable mean long‐term utility levels following ESS and often return to a health state comparable to US population norms. Level of Evidence 2b. Laryngoscope, 124:19–23, 2014